Deformation analysis of pipe-jacking process for a large-section shallow-covered project crossing highway. Issue 5 (October 2021) - Zhen, L; Yu, W; Xu, W; Yue, X
Abstract: This paper introduces an engineering example of a large cross-section shallow soil covered rectangular pipe jacking of East-West double track crossing expressway. The cross-section size of pipe jacking is 9.90m × 8.15m, the length of single section is 1.5m, the through length of east line and west line is 80m, and the thickness of soil covering is 2.48 ∼3.13M. In order to reduce the impact of pipe jacking construction on the expressway, measures such as setting of the frontal jacking pressure, the control of the friction resistance of the slurry sleeve, the control of the slurry pressure and the settings of φ 824 ×12@1100 steel pipe concrete curtain. The vertical displacement of the steel pipe curtain and the displacement of the highway pavement was monitored. The results show that the road surface heave is controlled within 3cm: the maximum heave of the north shoulder near the pipe curtain launching shaft is 27.8mm, the heave of the central road arch is 16.2mm ∼ 19.1mm, the maximum heave of the south shoulder near the receiving shaft is 12.7mm, and the maximum heave of each section is less than 1.5mm The position is the axis of pipe jacking machine. From the cross-sections of pipe jacking crossing, the range of transverse influence area of 5mm road uplift is about 2.0 ∼ 3.0 times the width of pipe jacking machine, and the range of transverse influence area of 10mm road uplift is 1.0 ∼ 2.0 times the width of pipe jacking machine. The monitoring results show that the construction parameters of pipe jacking are reasonable